The Role Of Law In Providing Protection To Women From Acts Of Violence - Rizki Permana Putra; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
Women constitute the demographic that is most susceptible to instances of physical, psychological, verbal, and sexual violence. Instances of violence against women have the potential to occur at any given moment and in any location. The individuals responsible for perpetrating acts of violence against women are not only unidentified individuals; Rather, a significant number of offenders were discovered to be individuals who had close relationships with the victims, including spouses, parents, and siblings. The prevalence of violence against women is influenced by a multitude of circumstances and reasons that drive offenders to engage in such behavior. The Indonesian legal framework includes legislative provisions aimed at safeguarding women from acts of violence, a concerning trend that exhibits a consistent rise in reported incidents. This study employs both a legislative methodological framework and a conceptual approach. The present methodology is used to conduct an examination of the safeguarding measures for women as specified in Law 12 of the year 2022. The primary objective of this study is to investigate the extent to which the legal framework in Indonesia serves to safeguard women from various manifestations of violence. The findings derived from this study demonstrate that the legal framework in Indonesia actively contributes to the safeguarding of women from acts of violence, in accordance with relevant rules and legislation.